Tunable focus lens using eletroactive polymer - Ng, Fu Xing (2015)
Optical lenses with tunable focus capability have been intensively researched as it is much more compact, efficient and flexible as compared to traditional lenses. Recently, dielectric elastomer actuator (DEA), which is compact and lightweight, has been incorporated into the development of tunable lens. Despite having several advantages, it is not without weakness. Limited tuning range and stability is the key issue for tunable lens using DEA. In order to overcome the drawback of the tunable lens face with tunable lens using DEA, the DEA and lens are separated. This allows independent optimization. In the initial phase experiment is carried out to investigate the effect of pressure on the focal length change. After which, an encapsulation will be included to test the effect of dielectric oil on the focal length change. Preliminary results show a focal length variation of 137%. It is shown that with optimization of pressure and avoiding breakdown, a larger focusing range is possible.